Efeitos do armazenamento, temperatura, lixiviação e ácido Giberélico na percentagem e velocidade de emergência de bulbilhos de alho (Allium sativum L.) - Costa, Nivaldo Duarte (1987)
A laboratory and field experiment was carried out in order to study the effects of different storage periods under different temperatures, lixiviation and gibberellic acid (GA3) on the speed and percentage of germination of garlic cloves [...]